Students Problems in Developing Speaking Skill at the tenth Grade SMA Darul Hijrah Putra - Zannah*, Fathul; Noormaliah, Noormaliah; Hidayanti, Desi (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2024)
The objective of this research is describe the students problems in developing speaking skill at tenth grade SMA Darul Hijrah Putra Martapura In this research, the researcher uses descriptive qualitative as the research design. The population of this research is students at SMA Darul Hijrah Putra Martapura and the samples of this research are 36 students from class X SMA. the samples are selected based on the problem formulation. This research uses questionnaire and interview as the instrument. The finding shows that students problem: nothing to say 58,33, mother-tongue use 80,55, difficult to express ideas verbally 58,33, limited vocabulary 72,22, limited ability of grammar 72,22, focused on grammar 61,11.